Price trends in greenhouse tomato and pepper and choice of adoptable technology - García-Martínez, M.C.; Caballero Villar, P.; Fernández-Zamudio, M.A. (Spanish Journal of Agricultural Research, 2008)
Currently, intensive horticultural production in the Spanish Mediterranean region is strongly influenced by the liberalization of markets, which means farms must become more competitive and focus on consumer demands, such as product quality and health. The goals of the present work are to determine how the current economic situation of the tomato and pepper are reflected in the origin price, and to carry out an assessment of the technology available in the greenhouses. This study focuses on three principal Spanish regions of greenhouse horticultural production, located in Almería, Murcia and the South of Alicante (South-East Spain). Trend and seasonality of origin prices have been determined, and the ARIMA models have been used to predict pepper prices in Almería. Our analysis resulted in the following: the development of purchasing power, based on the price trends of the studied varieties; seasonal indices are developed to assist decision-making with respect to production schedules, choice of varieties and use of heating; finally, prediction is used to assist in planning the productive and commercial activity for the following season. There are two major determinants of technology adoption which include the fundamental elements of the equipment (heating and substrate) and the different production modes, like integrated production in different certified modes, and ecological production.